A simple structured filtering dielectric resonator antenna - Sahu B.; Tripathi P.; Singh S.; Meshram M.K.; Singh S.P. (My University, 2025)
Simulation study of a simple structured filter-antenna combination using a dielectric resonator (DR) is presented in this paper. The coupling between the input and output ports of the filter occurs due to alumina ceramic acting as DR and same DR is utilized as an antenna. The proposed filtering dielectric resonator antenna (DRA) provides good impedance matching. The simulated -10 dB reflection coefficient bandwidth of the proposed filtering DRA is found to be 930 MHz (11.34 - 12.27 GHz) with centre frequency of 11.88 GHz. The simulated realized gain of the proposed filtering DRA varies from 4.8 dB to 5.4 dB over its operating frequency band. The proposed filtering DRA can find potential application in satellite, radar and wireless communication. © 2016 IEEE.